2016
DOI: 10.1136/neurintsurg-2016-012631
|View full text |Cite
|
Sign up to set email alerts
|

Association of clot burden score with radiographic and clinical outcomes following Solitaire stent retriever thrombectomy: analysis of the SWIFT PRIME trial

Abstract: The combination of IV thrombolysis and stent retriever thrombectomy with the Solitaire device is highly effective in achieving successful recanalization and a good clinical outcome throughout the entire range of CBS values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
8
1
Order By: Relevance
“…Additionally, clots with a higher proportion of fibrin demonstrate more pronounced contrast uptake than those rich in red blood cells after prolonged exposure; however, they could not be differentiated after initial contrast exposure. 13 The correlation between thrombus density on NCCT and SR using IVT, intraarterial thrombolysis and mechanical thrombectomy has been reported, 5,14,15 and a recent systematic review concluded that the hyperdense artery sign on NCCT is associated with red blood cell-rich thrombus and better successful recanalization rates. 6 Other studies have failed to confirm these findings, however, and overall the literature has been conflicting with some studies showing no association between clot density and recanalization with stent retrievers or aspiration.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, clots with a higher proportion of fibrin demonstrate more pronounced contrast uptake than those rich in red blood cells after prolonged exposure; however, they could not be differentiated after initial contrast exposure. 13 The correlation between thrombus density on NCCT and SR using IVT, intraarterial thrombolysis and mechanical thrombectomy has been reported, 5,14,15 and a recent systematic review concluded that the hyperdense artery sign on NCCT is associated with red blood cell-rich thrombus and better successful recanalization rates. 6 Other studies have failed to confirm these findings, however, and overall the literature has been conflicting with some studies showing no association between clot density and recanalization with stent retrievers or aspiration.…”
Section: Discussionmentioning
confidence: 98%
“…Although thrombus length is strongly associated with successful recanalization with intravenous tPA therapy, the predictive power of thrombus size in determining successful reperfusion in EVT appears to be diminished (14). The results of recent RCTs showed that there was no correlation between the clot burden score (using clot volume and length) and the effects of EVT (72, 73). Thrombus composition and its associated pathogenesis can be visualized by CT or MRI.…”
Section: Specific Diagnostic and Therapeutic Considerations In Evt Fomentioning
confidence: 99%
“…The results of the studies were inconsistent ( Table 2 ). It might be because of the different mechanical devices used, different methods used to determine thrombus size, and small number of cases included [ 21 , 25 - 30 ]. However, in a recent study of a relatively large number of patients who were treated with a stent retriever, higher clot burden scores were associated with increased likelihood of recanalization [ 2 ].…”
Section: Prediction Of Recanalization Based On Thrombus Sizementioning
confidence: 99%